Definitive radiation therapy for cervical cancer: Non-white race and public insurance are risk factors for delayed completion, a pilot study - Shariska S. Petersen; Samfee Doe; Thomas Buekers (Elsevier, 2018)
This is a pilot study to assess whether racial disparities exist in time to initiation and completion of external beam pelvic radiation therapy and brachytherapy in cervical cancers treated with definitive chemoradiation.A retrospective analysis was conducted on all cervical cancer patients treated with definitive radiotherapy between 2006 and 2016 at a single institution. Patient demographics including age, race, insurance status and stage at diagnosis were obtained. Analyses were performed according to the following definitions of wait times: interval from pathologic diagnosis of cervical cancer to (Siegel et al., 2016) initiation of radiation therapy, (Yoo et al., 2017) completion of external beam radiation therapy and (DeSantis et al., 2016) completion of external beam radiation therapy plus brachytherapy if indicated.Of 50 women, 21 self-identified as white, 25 as black and 4 as Hispanic. Due to small numbers, Hispanic women were included with black women as a non-white group. The average age was 52 years for women in this cohort. Mean days to initiation of radiation therapy were 41.8 days: 33.7 days among white patients versus 47.8 days for non-white patients (p-value 0.101). Mean days from diagnosis to completion of external beam pelvic radiation therapy were 81.3 days: 70.9 days among white patients versus 88.9 days among non-white patients (p-value 0.006). Non-white patients were more likely to have public insurance, which was also associated with a longer time to completion of radiation treatment.We conclude that non-white patients experienced delays to completing external beam radiation therapy, which was no longer present after adjusting for insurance status. Keywords: Cervical cancer, Disparities, Radiation therapy